Aktivitas Antibakteri Kombinasi Ampisilin Dan 10 Tanaman Obat Terhadap Escherichia Coli ResistenDan Methicillin Resistant Staphylococcus Aureus - Prasetyo, Muhammad Nur, Ratna Yuliani, M.Biotech. St (2016)
Infections caused bacteria Methicillin Resistant Staphylococcus aureus (MRSA) and Escherichia coli so many occur, MRSA and E. coli reported resistant to some antibiotic, one of them is ampicillin. Ampicillin combined with leaf extract of cashew nut shell fruit cashew nuts, betel leaves, papaya leaves, basil, garlic bulbs, nutmeg, clove, sappan wood, and galangal rhizome containing antimicrobial activity to enhance antibacterial activity of ampicillin against MRSA and E. coli. This study to determined antibacterial activity of a combination by ampicillin and 10 extracts of medicinal plants and knowing compounds identity contained in extract that has antibacterial activity of the largest. Extraction was carried out using maceration with 96% ethanol as solvent. Ampicillin sensitivity test, test activities extracts and test combine activity using agar diffusion method, which uses disk attached to media Mueller Hinto inoculated test bacteria. Each media will be given control antibiotic and control solvent. The extract has antibacterial high potency tested with thin-layer chromatography (TLC). Results of the most potent activity extract against MRSA is an sappan wood extract while E. coli is an clove extract. Combination test of ampicillin showed activity increased after combined with extract against MRSA and E. coli bacteria. TLC results obtained from sappan wood extract is thought to contain brazilin.